Hollowing out MOFs: hierarchical micro- and mesoporous MOFs with tailorable porosity via selective acid etching12. Issue 10 (21st August 2017) - Koo, Jaehyoung; Hwang, In-Chul; Yu, Xiujun; Saha, Subhadeep; Kim, Yonghwi; Kim, Kimoon
Abstract : We report a new strategy for the synthesis of robust hierarchical micro- and mesoporous MOFs from water stable MOFs via a selective acid etching process. Abstract : We report a new strategy for the synthesis of robust hierarchical micro- and mesoporous MOFs from water stable MOFs via a selective acid etching process. The process is controlled by the size-selective diffusion of acid molecules through the MOF windows. This method enables the fine-tuning of the porosity of hierarchical MOFs, allowing for the generation of well-defined mesopores with high mesopore volume. Because of the size-selective diffusion of acid molecules, the inherent crystallinity and external morphology of the resulting MOFs are well-maintained after acid treatment. This novel strategy may provide an alternative route towards the synthesis of diverse hierarchical MOFs.